Blogging Activism of Young Educated and Global Women in Tunisia and Vietnam: a two-case study - Mai, Yên; Laine, Sofia (PARTECIPAZIONE E CONFLITTO, 2017)
This article studies the blogging activism of two young, educated women who grew up in societies that emphasize traditional values. Through their blogging activities, these females embody a space for identity creation and recovery, and challenge the obedience to gender norms, authority, and religion in their home cultures. Though coming from two different societies (Tunisia and Vietnam), both subjects identify themselves within a global citizenship framework through their everyday life and blogging that emphasizes connection, harmony, and respect for diversity. The method of this study is a combination of autoethnography, ethnography and blog research, transforming the researcher also into the subject of analysis. Personal experiences and life stories of the author are analysed in conjunction with data provided by the informant. The data includes personal blogs, writings, drawings, interviews and collective discus-sions, which provide an intimate approach to the inner life of the study subjects. Through our analysis we conclude that the blogging may open new political spaces for culturally oppressed differences and become a practical space for girls to exercise their own control of self-representation. Girls who have difficulties in being heard or acknowledge in their everyday circumstances may create new types of expressions and ac-tivism through their blogging activity, where they find new belonging and strengthen their identity for-mation